Marriage Registration As a Form Of Maṣlaḥah Mursalah - Rahman, Fadhly Kharisma (Maqasid: Jurnal Studi Hukum Islam, 2023)
Registration of marriages can be categorized as a new phenomenon because in its history during the time of the Prophet there had never been registration and bookkeeping of marriages, divorces and reconciliation. Bookkeeping during the time of the Prophet was only a matter of bookkeeping in the Qur'an, whereas explicitly in the text there is an order to record and record books in the aspect of muamalah or selling buying and selling transactions. This article attempts to explore more deeply the issue of marriage registration within the framework of maslahah murlah. The author's findings are that marriage registration is in line with sharia provisions , namely creating benefits and preventing harm. The first dharuriy need is the benefit of maintaining religion. Marriage registration is seen as able to protect and maintain religious benefits. Second , benefit in protecting and guarding the soul. This can be seen from the psychological condition of the wife and children who are calmer, because without a marriage book a child cannot make a birth certificate. Third , benefit in maintaining reason. Marriage registration is very important for children's psychology, because with a marriage book, the child will feel calm because he is the legitimate child of both parents, so he will be confident in developing his mind to the maximum. Fourth , maintaining offspring. By registering a marriage, mixing between two people of different sexes is considered not adultery, so that children born from this relationship are considered valid and have clear identities and can be proven by law. Fifth, maintain property. By recording a marriage, the identity of the child born has clarity, so that when the parents die, the child will get his inheritance rights, so that the assets from the marriage can be maintained.